2022
DOI: 10.1126/sciadv.abm9427
|View full text |Cite
|
Sign up to set email alerts
|

Eprenetapopt triggers ferroptosis, inhibits NFS1 cysteine desulfurase, and synergizes with serine and glycine dietary restriction

Abstract: The mechanism of action of eprenetapopt (APR-246, PRIMA-1 MET ) as an anticancer agent remains unresolved, although the clinical development of eprenetapopt focuses on its reported mechanism of action as a mutant-p53 reactivator. Using unbiased approaches, this study demonstrates that eprenetapopt depletes cellular antioxidant glutathione levels by increasing its turnover, triggering a nonapoptotic, iron-dependent form of cell death known as ferroptosis. Deficiency in genes responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“… 390 396 Tumor cell lines carrying TP53 , TP53 mutations, or TP53 deletions responded to APR-246 treatment. 397 400 However, growing evidence suggests that APR-246 exerts its effects through a multitude of pathways independent of p53, 401 – 404 such as downregulating glutathione concentrations in tumor cells, 405 , 406 regulating oxidation-reduction homeostasis 407 409 in tumor cells to trigger ferroptosis, 410 412 and inducing endoplasmic reticulum stress 413 or unfolded protein responses. 414 …”
Section: Structure-based P53 Targetingmentioning
confidence: 99%
“… 390 396 Tumor cell lines carrying TP53 , TP53 mutations, or TP53 deletions responded to APR-246 treatment. 397 400 However, growing evidence suggests that APR-246 exerts its effects through a multitude of pathways independent of p53, 401 – 404 such as downregulating glutathione concentrations in tumor cells, 405 , 406 regulating oxidation-reduction homeostasis 407 409 in tumor cells to trigger ferroptosis, 410 412 and inducing endoplasmic reticulum stress 413 or unfolded protein responses. 414 …”
Section: Structure-based P53 Targetingmentioning
confidence: 99%
“…The restoration of wild-type TP53 expression triggers cell death by inducing apoptosis in tumor cells [ 112 ]. Eprenetapopt can also induce p53-independent cell death in the course of ferroptosis, a recently described cell death process [ 113 ].…”
Section: In the Grip Of Apoptosis—the Desired Future After Venetoclaxmentioning
confidence: 99%
“…Recent work identified that the small molecule pro-drug eprenetapopt (used interchangeably in our figures as APR-246) promotes ferroptosis in a range of cancer cells [49,50]. Of relevance, ferroptosis is suppressed in the presence of high levels the cystine-glutamate antiporter SLC7A11, which imports cystine across the plasma membrane, feeding the biosynthesis of the antioxidant glutathione.…”
Section: A Cellular Senescencementioning
confidence: 99%